β-Catenin Regulates Positive Selection of Thymocytes but Not Lineage Commitment - Yu, Qing (2007)
Positive selection and lineage commitment to the cytolytic or helper lineage of T cells result in coordinated expression of MHC class I-restricted TCR and CD8 coreceptor or MHC class II-restricted TCR and CD4 molecule. Positive selection signals also regulate the survival and generation of requisite numbers of cytolytic or Th cells. β-Catenin is the major transcriptional cofactor of T cell factor and plays a role in thymocyte development. In this study, using mice expressing stabilized β-catenin and mice with T cell-specific deletion of β-catenin, we show that β-catenin regulates positive selection, but not lineage commitment of thymocytes. Furthermore, β-catenin expression accelerates the timing of mature CD8 thymocyte generation such that CD4 and CD8 single-positive thymocytes mature with the same kinetics during development.